Adhesive material and light-curing adhesive for bonding polyimide
By introducing organopolysilazane into the bonding material to form Si-N long chains, the problem of difficulty in bonding of polyimide materials is solved, efficient and high-temperature resistance is achieved, and the flexibility of the photocured glue is improved.
Patent Information
- Application Number
- CN202411954750.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-04
AI Technical Summary
The prior art is difficult to effectively bond polyimide (PI) materials, especially due to their high chemical inertia, low surface energy and high strength rigidity, it is difficult for conventional adhesives to form a firm bonding structure.
An adhesive material including polyether polyol, isocyanate, hydroxyacrylic monomer and organopolysilazane is used. This material introduces Si-N long chains through reaction of amino groups with isocyanate groups, which significantly improves bonding and high temperature resistance.
It achieves excellent bonding properties to polyimide, improves the high temperature resistance and flexibility of photocured glue, has a tensile strength of up to 8.11MPa, and has a good bonding effect on difficult-to-adhesive materials.
Smart Images

Figure BDA0005215577050000021 
Figure BDA0005215577050000031 
Figure BDA0005215577050000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of bonding materials and relates to a bonding material and a light-curing adhesive for bonding polyimide. Background Art
[0002] PI (polyimide) is a material with high and low temperature resistance, high insulation, and low thermal expansion coefficient. It is widely used in various industries, especially in the field of speakers. In the central part of the speaker (voice coil, paper cone, and spring plate), PI material is a common voice coil material, but it is difficult to bond due to its special chemical structure and physical properties.
[0003] PI materials are chemically inert and their surface is not prone to chemical reactions with other substances, which makes it difficult for conventional adhesives to form a strong bonding structure with PI materials. The high melting point and thermal stability of PI materials also mean that the curing temperature of conventional adhesives may not reach the melting point of PI materials, making it difficult to achieve effective bonding. PI materials have low surface energy and are not easily wetted, resulting in problems with adhesives being unable to fully penetrate and diffuse onto the surface of PI materials, affecting the strength and reliability of the bonding. The high strength and rigidity of PI materials make it difficult for them to undergo plastic deformation, resulting in a low contact area and bonding strength between the adhesive and PI materials.
[0004] At present, epoxy adhesives or silicone are mostly used for bonding PI materials. For example, CN114085491A discloses a polyetheretherketone modified epoxy resin composition and a preparation method thereof, which uses polyetheretherketone to improve the bonding strength between epoxy resin adhesive and PI film. In this paper, according to the test method (IPC-TM-6502.4.8), the peel strength test was carried out with PI material as the substrate. The peel strength of the embodiments is relatively high, but the curing condition is to place it in a hot air circulation oven at 180°C for 3 minutes. High temperature curing leads to high energy consumption and a relatively slow curing time.
[0005] Currently, epoxy AB glue is mostly used for PI materials used in speaker components, but this adhesive has poor environmental performance and slow curing. If you want to increase the curing rate, you need to heat it, which will lead to high energy consumption. If UV glue can be used to bond PI materials, it will have many advantages, including curing in more than ten seconds under light, environmental protection, energy saving and emission reduction, and the relevant performance can be adjusted according to the application scenario of the PI material.
[0006] Since UV adhesive is relatively poor in adhesion to PI materials, the introduction of organic silicon into the light-curing resin system can effectively improve the high temperature resistance and adhesion to PI materials, so the introduction of new polymer material organic polysilazane is used to improve the polyurethane acrylic resin. The application of organic polysilazane is introduced in detail in the research progress of application of polysilazane (Zhang Zongbo, Zeng Fan, Luo Yongming, etc., Organic Silicon Materials, 2013, 27(03): 216-222). It is mostly used in ceramic materials and coatings, but there is little research on it as a resin material. At present, it has not been found to be used for modifying polyurethane acrylic resin. Summary of the invention
[0007] In order to solve the above technical problems, the present application provides an adhesive material and a photocuring adhesive for bonding polyimide. The adhesive material has excellent bonding properties for polyimide and can also improve the high temperature resistance and flexibility of the photocuring adhesive.
[0008] In order to achieve the above technical effects, the present invention adopts the following technical solutions:
[0009] One of the purposes of the present invention is to provide a bonding material for bonding polyimide, wherein the bonding material comprises polyether polyol, diisocyanate, hydroxyl-containing acrylic monomer and organic polysilazane.
[0010] As a preferred technical solution of the present invention, the bonding material comprises, by mass fraction:
[0011]
[0012] As a preferred technical solution of the present invention, the structure of the organic polysilazane is shown as follows:
[0013]
[0014] Wherein, R1, R2 and R3 are independently any one of a hydrogen atom, a substituted or unsubstituted straight-chain or branched saturated alkyl group, a straight-chain or branched unsaturated alkyl group, a substituted or unsubstituted aromatic group, a hydroxyl group, an amino group, a carboxyl group or an aldehyde group, or a combination of at least two of them; R1, R2 and R3 are not hydrogen atoms at the same time; and n is a positive integer ranging from 2 to 1000.
[0015] As a preferred technical solution of the present invention, the polyether polyol includes any one of polypropylene glycol, polytetramethylene glycol, tetramethylene glycol-propylene oxide copolymer glycol, special polyether polyol or white polyether polymer polyol, or a combination of at least two thereof.
[0016] As a preferred technical solution of the present invention, the diisocyanate includes any one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate or lysine diisocyanate, or a combination of at least two thereof.
[0017] As a preferred technical solution of the present invention, the hydroxyl-containing acrylic monomer includes any one of hydroxyethyl methacrylate, hydroxypropyl methacrylate or pentaerythritol triacrylate, or a combination of at least two thereof.
[0018] As a preferred technical solution of the present invention, the bonding material also includes a catalyst.
[0019] As a preferred technical solution of the present invention, the mass fraction of the catalyst is 0.01-0.05%.
[0020] A second object of the present invention is to provide a photocurable adhesive, which includes the bonding material provided in the first object.
[0021] As a preferred technical solution of the present invention, the raw materials of the photocurable adhesive include, by mass fraction:
[0022]
[0023]
[0024] Compared with the prior art, the present invention has at least the following beneficial effects:
[0025] (1) The present invention provides an adhesive material and a photocuring adhesive for bonding polyimide, wherein the adhesive material has excellent bonding performance for polyimide and can also improve the high temperature resistance and flexibility of the photocuring adhesive;
[0026] (2) The present invention provides an adhesive material and a photocuring adhesive for bonding polyimide. The photocuring adhesive has a tensile strength of up to 8.11 MPa, an elongation at break of up to 621%, high flexibility, and a PC / PI peel strength of up to 1.95 N / mm. It also has a certain bonding effect on difficult-to-bond materials such as PET, Tetoron, and PEEK. DETAILED DESCRIPTION
[0027] The technical solution of the present application is further described below through specific implementation methods.
[0028] A specific embodiment of the present invention provides a bonding material for bonding polyimide, wherein the bonding material comprises polyether polyol, diisocyanate, hydroxyl-containing acrylic monomer and organic polysilazane.
[0029] In the present invention, the amino group of polysilazane reacts with the isocyanate group in diisocyanate to introduce the Si-N long chain into the polyurethane acrylate system, which can significantly enhance the bonding performance of the adhesive material to the PI material and improve the high temperature resistance of the adhesive itself.
[0030] In one specific embodiment of the present invention,
[0031] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0032] According to mass fraction, the bonding material includes:
[0033]
[0034]
[0035] Wherein, the mass fraction of the polyether polyol can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or 65%, etc., the mass fraction of the diisocyanate can be 20%, 25%, 30%, 35%, 40%, 45% or 50%, etc., the mass fraction of the hydroxyl-containing acrylic monomer can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc., the mass fraction of the organopolysilazane can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc., but are not limited to the listed values, and other values not listed within the above numerical ranges are equally applicable.
[0036] In one specific embodiment of the present invention, the structure of the organopolysilazane is shown as follows:
[0037]
[0038] Wherein, R1, R2 and R3 are independently any one of hydrogen atom, substituted or unsubstituted straight chain or branched saturated alkyl, straight chain or branched unsaturated alkyl, substituted or unsubstituted aromatic group, hydroxyl group, amino group, carboxyl group or aldehyde group or a combination of at least two thereof, R1, R2 and R3 are not hydrogen atom at the same time, and n is a positive integer of 2 to 1000. n can be 2, 10, 20, 50, 100, 200, 500, 800 or 1000, etc., but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0039] In a specific embodiment of the present invention, the substituted or unsubstituted straight-chain or branched saturated alkyl group can be methyl, ethyl, n-propyl, isopropyl, n-butyl, 2-butyl, isobutyl, n-pentyl, n-hexyl or n-octyl, etc.
[0040] In a specific embodiment of the present invention, the straight-chain or branched unsaturated alkyl group can be a group in which at least one carbon-carbon single bond of ethyl, n-propyl, isopropyl, n-butyl, 2-butyl, isobutyl, n-pentyl, n-hexyl or n-octyl is replaced by a carbon-carbon double bond or a carbon-carbon triple bond.
[0041] In a specific embodiment of the present invention, the substituted or unsubstituted aromatic group may be, for example, phenyl, 2-methylphenyl, 4-chlorophenyl, 4-hydroxyphenyl, naphthyl, 2-furyl or 2-pyridyl.
[0042] In a specific embodiment of the present invention, the substituent can be methyl, ethyl, vinyl, ethynyl, phenyl, benzyl, hydroxyl, amino, carboxyl or aldehyde.
[0043] In a specific embodiment of the present invention, the organic polysilazane may be methyl polysilazane, poly (1,1) dimethyl silazane or polyvinyl silazane.
[0044] In a specific embodiment of the present invention, the polyether polyol includes any one of polypropylene glycol, polytetramethylene glycol, tetramethylene glycol-propylene oxide copolymer glycol, special polyether polyol or white polyether polymer polyol, or a combination of at least two thereof.
[0045] In a specific embodiment of the present invention, the diisocyanate includes any one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate or lysine diisocyanate, or a combination of at least two thereof.
[0046] In a specific embodiment of the present invention, the hydroxyl-containing acrylic monomer includes any one of hydroxyethyl methacrylate, hydroxypropyl methacrylate or pentaerythritol triacrylate, or a combination of at least two thereof.
[0047] In one specific embodiment of the present invention, the bonding material further includes a catalyst.
[0048] In a specific embodiment of the present invention, the mass fraction of the catalyst is 0.01-0.05%, such as 0.01%, 0.02%, 0.03%, 0.04% or 0.05%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] In one embodiment of the present invention, the catalyst may be chelated tin, monobutyl tin or dibutyl tin, such as dibutyl tin dilaurate.
[0050] In one specific embodiment of the present invention, a method for preparing an adhesive material for bonding polyimide may include:
[0051] The polyether polyol is dehydrated, mixed with an organic polysilazane, reacted under a protective atmosphere, and diisocyanate is added dropwise to the reaction system to obtain an -NCO-terminated polyurethane prepolymer containing polysilazane;
[0052] The -NCO-terminated polyurethane prepolymer containing polysilazane is mixed with a hydroxyl-containing acrylic monomer and a catalyst, and reacted under a protective atmosphere to obtain the bonding material.
[0053] In a specific embodiment of the present invention, the dehydration treatment method can be carried out by stirring and dehydrating for 1.5 to 2 hours at 110 to 120° C. and a vacuum degree of ≥-0.095 MPa.
[0054] In a specific embodiment of the present invention, the temperature for the reaction of polysilazane and diisocyanate monomer may be 50-70° C., and the reaction time may be 2-5 hours.
[0055] In a specific embodiment of the present invention, the reaction temperature of the -NCO terminated polyurethane prepolymer containing polysilazane and the hydroxyl-containing acrylic monomer can be 60 to 95° C., and the reaction time can be 2 to 5 hours.
[0056] In a specific embodiment of the present invention, the protective atmosphere can be any one of nitrogen, argon or helium.
[0057] A specific embodiment of the present invention provides a photocurable adhesive, which includes the bonding material provided in one of the purposes.
[0058] In a specific embodiment of the present invention, the raw materials of the light-curing adhesive include:
[0059]
[0060] Among them, the mass fraction of the adhesive material can be 30%, 35%, 40%, 45%, 50%, 55% or 60%, etc., the mass fraction of the diluent monomer can be 35%, 40%, 45%, 50% or 55%, etc., the mass fraction of the photoinitiator can be 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., the mass fraction of the adhesion promoter can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc., but are not limited to the listed values, and other values not listed within the above numerical ranges are equally applicable.
[0061] In a specific embodiment of the present invention, the diluent monomer includes any one or a combination of at least two of isobornyl acrylate (IBOA), tetrahydrofuranyl acrylate (THFA), acryloyl morpholine (ACMO), dimethylacrylamide (DMAA), 3,5,5-trimethylcyclohexyl acrylate (TMCHA), lauric acid acrylate (LA) or isooctyl acrylate (2-EHA).
[0062] In a specific embodiment of the present invention, the photoinitiator is selected from any one of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, 2,4,6-trimethylbenzoyl-di (p-tolyl) phosphine oxide, 1-hydroxycyclohexyl phenyl ketone or 4-dimethylamino-ethyl benzoate, or a combination of at least two thereof.
[0063] In a specific embodiment of the present invention, the adhesion promoter includes any one of acrylic acid, phosphate ester or β-acryloxy propionic acid or a combination of at least two thereof.
[0064] In one specific embodiment of the present invention, the preparation method of the photocurable adhesive may be:
[0065] The adhesive material, diluent monomer, photoinitiator and adhesion promoter are non-invasively homogenized and mixed until the adhesive solution is clear and uniform.
[0066] In a specific embodiment of the present invention, the conditions of non-intrusive homogeneous mixing can be adjusted according to the specific addition ratio of each component and the specific material selected, and are not further limited here. As an example, the mixing time is not less than 10 minutes, the revolution ratio is set to 50%, the speed is set to revolution: rotation = 1300:750, and the mixing environment is set to a vacuum environment.
[0067] Example 1
[0068] This embodiment provides a bonding material for bonding polyimide. The bonding material includes, by mass fraction, 20% polypropylene glycol, 20% methyl polysilazane, 50% diphenylmethane diisocyanate, 9.97% hydroxyethyl methacrylate and 0.03% catalyst dibutyltin dilaurate.
[0069] The preparation method of the bonding material comprises:
[0070] Add an appropriate amount of polypropylene glycol into a three-necked flask, and stir and dehydrate for 2 hours at a temperature range of 120°C and a vacuum degree of ≥-0.095MPa;
[0071] In a four-necked flask, add 20% of vacuum-dehydrated polypropylene glycol and 20% of methyl polysilazane, introduce nitrogen at a reaction temperature of 60°C, add 50% of diphenylmethane diisocyanate into the four-necked flask using a constant pressure funnel, react for 2 hours, and obtain a -NCO-terminated polyurethane prepolymer containing polysilazane;
[0072] The reaction temperature was raised to 75° C., 9.97% of hydroxyethyl methacrylate and 0.03% of dibutyltin dilaurate as a catalyst were added to the flask, and the reaction was carried out for 2 hours to obtain a polysilazane-modified photocurable resin.
[0073] This embodiment also provides a photocurable adhesive, and its preparation method includes, by mass fraction:
[0074] 50% of the above adhesive material, 15% of acryloylmorpholine, 30% of 3,5,5-trimethylcyclohexyl acrylate, 2% of acrylic acid and 3% of diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide were added to a centrifugal cup, and the vacuum mode was set in a non-invasive homogenizer, the stirring time was set to 10 min, the mixing revolution and rotation ratio was set to 50%, and the rotation speed was set to revolution: rotation = 1300: 750 to obtain a uniformly mixed light-curing adhesive.
[0075] Example 2
[0076] The present embodiment provides a bonding material for bonding polyimide. The bonding material comprises, by mass fraction, 35% polytetramethylene glycol, 5% methyl polysilazane, 40% isophorone diisocyanate, 19.95% pentaerythritol triacrylate and 0.05% catalyst dibutyltin bis(acetylacetonate).
[0077] This embodiment also provides a photocuring adhesive, and the composition of the photocuring agent includes, by mass fraction:
[0078] 35% of the above adhesive material, 10% of isobornyl acrylate, 25% of tetrahydrofuran acrylate, 20% of dimethylacrylamide, 5% of phosphoric acid ester, and 5% of 2,4,6-trimethylbenzoyl-di(p-tolyl)phosphine oxide.
[0079] The preparation method of the bonding material and the light-curing adhesive is the same as that of Example 1.
[0080] Example 3
[0081] The present embodiment provides a bonding material for bonding polyimide. The bonding material includes, by mass fraction, 10% tetrahydrofuran-propylene oxide copolymer glycol, 20% poly (1,1)-dimethylsilazane, 49.95% diphenylmethane diisocyanate, 20% hydroxypropyl methacrylate and 0.05% catalyst dibutyltin dilaurate.
[0082] This embodiment also provides a photocuring adhesive, and the composition of the photocuring agent includes, by mass fraction:
[0083] 30% of the above adhesive material, 10% of isobornyl acrylate, 25% of tetrahydrofuran acrylate, 20% of dimethylacrylamide, 5% of β-acryloxypropionic acid, and 10% of 1-hydroxycyclohexyl phenyl ketone.
[0084] The preparation method of the bonding material and the light-curing adhesive is the same as that of Example 1.
[0085] Example 4
[0086] This embodiment provides a bonding material for bonding polyimide. The bonding material includes, by mass fraction, 64.98% tetrahydrofuran-propylene oxide copolymer glycol, 5% poly (1,1)-dimethylsilazane, 20% diphenylmethane diisocyanate, 10% hydroxypropyl methacrylate and 0.02% catalyst dibutyltin dilaurate.
[0087] This embodiment also provides a photocuring adhesive, and the composition of the photocuring agent includes, by mass fraction:
[0088] 60% of the above adhesive material, 10% of isobornyl acrylate, 10% of 3,5,5-trimethylcyclohexyl acrylate, 15% of lauric acid acrylate, 3% of β-acryloxypropionic acid, and 2% of 4-dimethylamino-ethyl benzoate.
[0089] The preparation method of the bonding material and the light-curing adhesive is the same as that of Example 1.
[0090] Comparative Example 1
[0091] In this comparative example, except that methyl polysilazane is not added, other conditions are the same as those of Example 1.
[0092] Comparative Example 2
[0093] In this comparative example, except that methyl polysilazane is replaced by silane coupling agent γ-glycidyloxypropyltrimethoxysilane, other conditions are the same as those of Example 2.
[0094] The peel strength, tensile strength and elongation at break of the photocurable adhesives provided in Examples 1-4 and Comparative Examples 1 and 2 were tested, and the results are shown in Table 1.
[0095] Peel strength test: The testing instrument tensile machine (HZ-1003C) is used to bond a 10mm wide film to a PC sheet, and the peel strength is tested at room temperature and high temperature.
[0096] Mechanical properties test: The test instrument is a tensile testing machine (HZ-1003C). Dumbbell-shaped specimens are prepared, clamped with a fixture, and stretched at 100 mm / min.
[0097] Table 1
[0098]
[0099] By comparing the examples with the comparative examples, it is found that the comparative examples have lower bonding strength to PI than the examples. By comparing the relevant properties of Example 1 with those of Comparative Example 1, it is found that the organic polysilazane-modified UV adhesive (Example 1) has better mechanical properties than the unmodified UV adhesive (Comparative Example 1), and also has better bonding performance to PI, with a peel strength of up to 1.95 N / mm, and still has bonding strength at high temperatures. However, Comparative Example 1 has almost no bonding strength to PI, with a peel strength as low as 0.29 N / mm, and its performance to other film materials is also relatively inferior.
[0100] By comparing Example 2 with Comparative Example 2, it is found that the comprehensive performance of the polysilazane-modified UV adhesive is better than that of the silane coupling agent-modified UV adhesive. The PI / PC peel strength, PC / PET peel strength, and glass / Tetoron peel strength of Example 2 are 1.32 N / mm, 2.23 N / mm, and 1.81 N / mm, respectively, which are higher than those of Comparative Example 2. The high-temperature PI / PC peel strength and mechanical properties of Example 2 are also better than those of Comparative Example 2.
[0101] The applicant declares that the present invention illustrates the detailed process equipment and process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process equipment and process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A bonding material for bonding polyimide, characterized in that: The bonding material comprises polyether polyol, diisocyanate, hydroxyl-containing acrylic monomer and organic polysilazane.
2. The adhesive material according to claim 1, characterized in that According to mass fraction, the bonding material includes:
3. The adhesive material according to claim 1, characterized in that: The structure of the organopolysilazane is shown below: Wherein, R1, R2 and R3 are independently any one of a hydrogen atom, a substituted or unsubstituted straight-chain or branched saturated alkyl group, a straight-chain or branched unsaturated alkyl group, a substituted or unsubstituted aromatic group, a hydroxyl group, an amino group, a carboxyl group or an aldehyde group, or a combination of at least two of them; R1, R2 and R3 are not hydrogen atoms at the same time; and n is a positive integer ranging from 2 to 1000.
4. The adhesive material according to claim 1, characterized in that: The polyether polyol includes any one of polypropylene glycol, polytetramethylene glycol, tetramethylene glycol-propylene oxide copolymer glycol, special polyether polyol or white polyether polymer polyol, or a combination of at least two thereof.
5. The adhesive material according to claim 1, characterized in that The diisocyanate includes any one of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, dicyclohexylmethane diisocyanate, hexamethylene diisocyanate or lysine diisocyanate, or a combination of at least two thereof.
6. The adhesive material according to claim 1, characterized in that: The hydroxyl-containing acrylic monomer includes any one of hydroxyethyl methacrylate, hydroxypropyl methacrylate or pentaerythritol triacrylate or a combination of at least two thereof.
7. The adhesive material according to claim 1, characterized in that The bonding material also includes a catalyst.
8. The adhesive material according to claim 1, characterized in that The mass fraction of the catalyst is 0.01-0.05%.
9. A light-curing adhesive, characterized in that: The photocurable adhesive comprises the bonding material according to any one of claims 1 to 8.
10. The light-curing adhesive according to claim 9, characterized in that: According to mass fraction, the raw materials of the photocurable adhesive include:
Citation Information
Patent Citations
Polyether-ether-ketone modified epoxy resin composition and preparation method thereof
CN114085491A